PENGARUH PERMAINAN KASTI TERHADAP KEMAMPUAN GERAK DASAR SISWA SEKOLAH DASAR KELAS BAWAH - Puspitawati, Isti Dwi; Jaenudin, Muhamad Ade (Universitas Pendidikan Ganesha, 2020)
Basic movement is an ability that physical education teachers must serve carefully. Providing opportunities to practice movement skills is the main key. The purpose of this study was to examine the effect of learning the traditional game of kasti on the basic abilities of lower grade elementary school students. The study was conducted with a True-experimental randomized pre-test post-test design. Participants consisted of 25 low-grade elementary school students. The treatment was carried out for 16 meetings. Basic movement ability is carried out by conducting tests and measurements of the ability to throw a target, throw a catch, hit a ball, and a 50m run test. Data were analyzed using the T-test. The results of the analysis show a significant level of 0.494. This means that learning the traditional game of kasti has no significant effect on basic skills. The conclusion that can be drawn from this research is that it is necessary to modify the learning process so that the objectives can be achieved.